Mitochondrial fission – a drug target for cytoprotection or cytodestruction?. Issue 3 (21st April 2016) - Rosdah, Ayeshah A.; K. Holien, Jessica; Delbridge, Lea M. D.; Dusting, Gregory J.; Lim, Shiang Y.
Abstract: Mitochondria are morphologically dynamic organelles constantly undergoing processes of fission and fusion that maintain integrity and bioenergetics of the organelle: these processes are vital for cell survival. Disruption in the balance of mitochondrial fusion and fission is thought to play a role in several pathological conditions including ischemic heart disease. Proteins involved in regulating the processes of mitochondrial fusion and fission are therefore potential targets for pharmacological therapies. Mdivi‐1 is a small molecule inhibitor of the mitochondrial fission protein Drp1. Inhibiting mitochondrial fission with Mdivi‐1 has proven cytoprotective benefits in several cell types involved in a wide array of cardiovascular injury models. On the other hand, Mdivi‐1 can also exert antiproliferative and cytotoxic effects, particularly in hyperproliferative cells. In this review, we discuss these divergent effects of Mdivi‐1 on cell survival, as well as the potential and limitations of Mdivi‐1 as a therapeutic agent.